Combined effects of anisotropy and tension–compression asymmetry on the torsional response of AZ31 Mg. (April 2015) - Chandola, Nitin; Lebensohn, Ricardo A.; Cazacu, Oana; Revil-Baudard, Benoit; Mishra, Raja K.; Barlat, Frédéric
Abstract: In this paper it is demonstrated that only by accounting for the combined effects of anisotropy and tension–compression asymmetry at polycrystal level, it is possible to explain and accurately predict the room-temperature torsional response of a strongly textured AZ31 Mg material. This is shown by using two modeling frameworks, namely: a viscoplastic self-consistent (VPSC) polycrystal model, and a macroscopic plasticity model based on an yield criterion, developed by Cazacu et al. (2006), that accounts for both orthotropy and tension–compression asymmetry in plastic flow. It is shown that unlike Hill's (1948) criterion, the latter macroscopic criterion quantitatively predicts the experimental results, namely: that the sample with axial direction along the rolling direction contracts, while the sample with axial direction along the normal direction elongates. Moreover, it is demonstrated that these experimentally observed axial strain effects can be quantitatively predicted with the VPSC polycrystal model, only if both slip and twinning are considered operational at single crystal level. On the other hand, if it is assumed that the plastic deformation is fully accommodated by crystallographic slip, the axial strains predicted by VPSC are very close with that predicted with Hill (1948) criterion, which largely underestimates the measured axial strain in the rolling direction, and predicts zero axial strain in the normal direction.